Girls in Trouble with the Law - Schaffner, Laurie (Book collections on Project MUSE., 2006)
Juvenile arrest rates in the United States have declined over the past decade, yet the percentage of girls in trouble with the law increased. Girls now enter the juvenile legal system for violent offenses in addition to minor violations for which previous generations of young women have always been detained. In Girls in Trouble with the Law, sociologist Laurie Schaffner takes us inside female detention centers and explores the worlds of those who are incarcerated. Across the country, she finds t.